FEEDBACK THAT SPEAKS: UNCOVERING STUDENTS’ PERCEPTIONS TO CORRECTIVE FEEDBACK IN FORMAL SPEAKING CLASS - Muhammad Herdiyansyah; Soni Mirizon (ENGLISH EDUCATION STUDY PROGRAM, FACULTY OF TEACHER TRAINING AND EDUCATION, UNIVERSITAS SRIWIJAYA, 2025)
This study examines how students feel about receiving corrective feedback from lecturers in the Speaking for Formal Interaction course and how it helps them become more proficient speakers. English education students participated in the study, which used a case study design. After being gathered via focus groups and questionnaires, the data was subjected to a thematic analysis. According to the findings, students believe that corrective feedback is crucial, particularly in formal settings. Direct correction was preferred by 27.4% of the 95 respondents, followed by recast (26.3%) and metalinguistic feedback (21.1%), indicating a preference for clear, direct feedback. This is corroborated by the fact that 12 out of 20 FGD participants preferred Direct Correction due to its advantages for clarity and retention. Students of all proficiency levels emphasized its linguistic and affective benefits. According to the study, in order to improve speaking performance, lecturers should establish a supportive environment and balance the different kinds of feedback.